Criminal Acts of Anarchism in The Perspective of Law No. 9 of 1998 - Wahyu Rasika Setya Arta; Wieke Dewi Suryandari (Journal Research of Social Science, Economics, and Management, 2023)
The democratic system adopted by Indonesia gives a high position and appreciation to the Indonesian people to participate in supervising the running of the Indonesian state by giving opinions orally and in writing. To manage and ensure this right, Regulation Number 9 of 1998 concerning the Opportunity of Offering Viewpoints in broad daylight was given. The approach used is a statutory approach (statute approach) and a conceptual approach (conceptual approach). The wellspring of information utilized is optional information. Information examination was completed in a subjective illustrative way. Concluding is carried out using the deductive method from general to specific, especially those related to the research topic, namely the Criminal Act of Anarchism Rallies in the Perspective of Law No. 9 of 1998. It found that demonstrations should be carried out by applicable regulations as stipulated in Law Number 9 of 1998 concerning the Freedom of Expressing Opinions in Public. If the demonstration runs in an orderly manner, then this is often known as a peaceful demonstration. However, in practice on the ground the demonstrations that were carried out often developed into acts of throwing and vandalism. The throwing and destruction of destroyed objects, as a result of the demonstrators' excessive desire to express opinions. Changes in peaceful conditions to anarchy are caused by throwing stones or other objects at places that have the potential to cause harm to public facilities, property, or loss of life.